Treatment of central venous in-stent restenosis with repeat stent deployment in hemodialysis patients. Issue 3 (May 2017) - Ronald, James; Davis, Bradley; Guevara, Carlos J.; Pabon-Ramos, Waleska M.; Smith, Tony P.; Kim, Charles Y.
Purpose: To report patency rates for stent deployment for treatment of in-stent stenosis of the central veins of the chest in hemodialysis patients. Materials and Methods: A retrospective analysis was performed on 29 patients who underwent 35 secondary percutaneous transluminal stent (PTS) deployments for in-stent stenosis within the central veins that were refractory to angioplasty and ipsilateral to a functioning hemodialysis access (in-stent PTS group). For comparison, patency data were acquired for 47 patients who underwent 78 successful percutaneous transluminal angioplasty (PTA) procedures for in-stent stenosis (in-stent PTA group) and 55 patients who underwent 55 stent deployments within native central vein stenosis refractory to angioplasty (native vein PTS group). Results: The 3-, 6-, and 12-month primary lesion patency for the in-stent PTS group was 73%, 57%, and 32%, respectively. The 3-, 6-, and 12-month primary patency for the in-stent PTA group was 70%, 38%, and 17% and for the native vein PTS group was 78%, 57%, and 26%, which were similar to the in-stent PTS group (p = 0.20 and 0.41, respectively). The 3-, 6-, and 12-month secondary access patency was 91%, 73%, and 65% for the in-stent PTS group. Sub-analysis of the in-stent PTS group revealed no difference in primary (p = 0.93) or secondary patency rates (p = 0.27) of bare metal stents (n = 23) compared with stent grafts (n = 12). Conclusions: Stent deployment for central vein in-stent stenosis refractory to angioplasty was associated with reasonable patency rates, which were similar to in-stent PTA and native vein PTS.